Comparison of mortality in mexican-american females and mexican american males following acute myocardial infarction - Brydges, Gary; Yacouby, Saeed; Eriksen, Lillian (Online Brazilian Journal of Nursing, 2004)
Acute myocardial infarction results in 7.2 million deaths per year world-wide.The treatment of AMI in the post-myocardial infarction period differs among the races and genders. This study investigated differences in mortality between Mexican American (MA) males and females, post-AMI who received BB therapy and those who did not receive BB therapy.Findings from this secondary analysis indicate that MA females experienced a higher mortality post-AMI compared to MA males. However, MA females taking BB therapy post-AMI had a reduced odds of mortality compared to MA males taking BB post-AMI. Interestingly, MA females were less likely to have received BB therapy post-AMI compared to MA males, despite its apparent benefit.